Screening of Trace Elements in Hair of the Female Population with Different Types of Cancers in Wielkopolska Region of Poland - Bogusław Czerny; Krzysztof Krupka; Marcin Ożarowski; Agnieszka Seremak-Mrozikiewicz (The Scientific World Journal)
Background. Cancer constitutes a major health problem worldwide. Thus, search for reliable and practical markers of the disease process remains the key issue of the diagnostic process. Objectives. The study aims at linking the trace element status of an organism, assessed by hair analysis, with the occurrence of cancer diseases. Material and Methods. Hair samples were collected from 299 patients with cancer diseases confirmed by a histopathological test and from 100 controls. Cancer patients were divided into three groups, depending on cancer type: hormone-dependent cancer, cancer of the alimentary tract, and cancer with high glycolytic activity. Mineral element analysis of hair was performed using an atomic emission spectrophotometer with inductively coupled plasma (ICP-OES) and inductively coupled plasma mass spectrometry (ICP-MS). Results. Statistically significantly lower concentrations of selenium, zinc, copper, germanium and boron, iron, and magnesium were observed in the three groups of cancer patients. Disturbance in the axis glucose-insulin and changes in concentrations of heavy metals and toxic elements were also noted. Conclusions. It seems safe to conclude that our results confirmed usefulness of hair element analysis in screening tests for the assessment of the biomarker of various cancer diseases in a female population.